Pengembangan Kemampuan Kinerja Karyawan Melalui Manajemen Pendidikan Dan Latihan - Solehan Solehan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
As company organizations develop, the need for training both functionally and technically is very necessary, apart from filling positions but also in order to meet the demands of work and service needs to the community. The problem is, how human resources (employees) are able to meet the expectations that have been set based on the vision and mission of an institution, organization or company, from this problem it seems that there needs to be a balance between company orientation. which will be directed at the performance that must be expressed by employees in realizing optimal organizational development. In this article, the research used is qualitative descriptive research, so it uses phenomena in which there are interview points. The phenomenon used as a reference is development, education and training as well as employee performance skills. This phenomenon is then used as a reference to determine the efforts made by institutions, organizations and companies to improve employee human resource capabilities. Based on the results of interviews that have been conducted, it can be seen that in improving the quality of human resources, the role of education and training is very necessary, especially after trainees have attended training, because to know employee development, continuous evaluation is needed to monitor progress. Education and training are very necessary in order to improve the abilities, professionalism and discipline of employees which are then used as the driving force for achieving the company's vision and mission.